Etická a neetická reklama : Vliv na spotřebitelské chování a vnímání značky - Špryslová, Zuzana; Filipová, Alena, 1965-; Zeman, Jiří; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis deals with the consumer's perception of ethical and unethical advertisements. Nowadays, advertising is an integral part of our daily lives and is also an integral part of the marketing mix of companies. The theoretical objectives of the thesis were to describe the historical development of advertising, to define the ethics of advertising, its effectiveness. In the practical part of the thesis, within the framework of a questionnaire survey, examples of ethical and unethical advertisements were set, to which the respondents were asked to react, to describe whether it had an ethical or unethical effect on them and what emotions it evoked in them.
Vedoucí práce: Alena Filipová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses